2014
DOI: 10.1097/01.prs.0000438456.75721.4e
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Case-Control Study on the Etiopathology of Kienböck Disease

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For the reconstruction of both skin and bone at the level of the DIP joint, there have been two previous case reports, an iliac crest bone graft and extended DMA flap in one patient and a free metacarpal bone graft and extended DMA flap in another. 12 13 Because bony reconstructions were performed using a nonviable bone graft in the former report, there were concerns with the risk of infection and nonunion. 13 For the latter report, the procedure of a free metacarpal bone graft seemed to be a complicated one, 12 and plain radiography was not presented initially after the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reconstruction of both skin and bone at the level of the DIP joint, there have been two previous case reports, an iliac crest bone graft and extended DMA flap in one patient and a free metacarpal bone graft and extended DMA flap in another. 12 13 Because bony reconstructions were performed using a nonviable bone graft in the former report, there were concerns with the risk of infection and nonunion. 13 For the latter report, the procedure of a free metacarpal bone graft seemed to be a complicated one, 12 and plain radiography was not presented initially after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…11 For reconstruction of both skin and bone at the distal interphalangeal (DIP) joint level, there is no report of reconstruction in such cases with the pedicled compound flap using DMA. 12 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Clinical study reports were designed involving all members of the team as easy-to-use data collection forms with sufficient and unambiguous data. The self-assessment questionnaire was developed by a multidisciplinary team consisting of two plastic surgeons, one psychiatrist, and a plastic surgery nurse with knowledge and experience in questionnaire design [ 14 , 15 ]. The self-assessment questionnaire included 12 items from the validated international pain outcome questionnaire (IPO) [ 16 ] and 5 items from the modified Brice questionnaire [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…3,4 The etiology is not well understood and remains controversial, but is traditionally thought to be related to trauma or anatomical www.journalchiromed.com factors. 5,6 Stahl et al 5 reported no relationship between the development of Kienbock disease and trauma (although commonly reported), hand-arm vibration, heavy manual labor, and comorbidities. They did, however, report an association with the use of oral corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with findings of osteonecrosis in other areas of the skeleton, as prolonged use of corticosteroids is the most common nontraumatic etiology. 5 Anatomical features may be a predisposing factor such as impaired blood supply and anatomical variation that results in increased shear force on the lunate such as negative ulnar variance. 1,3,7 The association with negative ulnar variance is controversial and not consistent worldwide.…”
Section: Introductionmentioning
confidence: 99%